Residual limb neuropathic pain association with neuroma, prosthetic, function, and participation outcomes in individuals living with a transtibial amputation: an exploratory study - Camille Fournier-Farley; Mathieu Boudier-Revéret; Dany H. Gagnon (Journal of Rehabilitation Medicine)
Objective: To determine the strength of the association between residual limb neuropathic pain intensity and the number of neuromas, prosthetic, functional, and participation outcomes, and assess whether ultrasound (US) biomarkers of neuromas differ between pain intensities.